Eficácia da ativação ultrassônica passiva do solvente na remoção de material obturador durante o retratamento endodôntico análise por microtomografia computadorizada - Michelon, Carina (2013)
The removal of pre-existing root canal filling is basic requirement for endodontic retreatment in order to reveal necrotic tissue debris and bacteria which may be responsible for periapical inflammation and by the treatment failure. The aim of this study was to evaluate the efficacy of passive ultrasonic activation (PUA) with use of organic solvent as an assistant method in removal of filling material during endodontic retreatment and determine a protocol for its utilization, using high-resolution micro-Computed Tomography (micro-CT). Thirty curved mesial roots of mandibular molars with isthmus area were instrumented and filled with gutta-percha and EndoFill (Dentsply-Maillefer, Ballaigues, Switzerland) through Tagger s hybrid technique. After 30 days, the filling material was removed with the ProTaper Retreatment rotary system (Dentsply-Maillefer, Ballaigues, Switzerland) and the root canals were prepared with the F1-F4 ProTaper instruments (Dentsply-Maillefer, Ballaigues, Switzerland). The specimens will be randomized into two groups according to the final irrigation protocol. In the Manual Group, the root canals were irrigated and agitated manually with Orange Oil solvent (Citrol, Biodinâmica, Ibiporã, Brazil), 2,5% Sodium Hypochlorite (NaOCl) (Biodinâmica, Ibiporã, Brazil) and 17% Ethylenediaminetetraacetic Acid (EDTA) (Biodinâmica, Ibiporã, Brazil). In the PUA Group, the specimens were submitted to PUA with Orange Oil solvent, 2,5% NaOCl and 17% EDTA. High-resolution micro-CT scans was used to select the sample, analyze the root filling and measure the volume of the remaining root filling material after each stage of the retreatment. The volume of remaining filling material was established and transformed into percentage in relation to total volume of filling material. The dates were statistically analyzed with a significance level set at α = 0.05. The Mann Whitney test was used to compare the percentage of remaining filling material between groups, for canal thirds in each retreatment step. The Friedman test was used to verify differences among root filling material and the successive retreatment stages at each canal segment in same group. The differences amongst the coronal, middle and apical third in the each group were analyzed with Friedman test. The Dunn test was performed as the post-hoc multiple comparison method. No significant differences between groups when rotary instrumentation (Stage 1) was considered (P > 0.05). None of the irrigation protocols removed completely the remains of the root canal filling. The use of Manual e PUA protocols decreases statistically the amount of remaining filling material compared to Stage 1 (P = 0.000). In the PUA Group, the root canals showed significantly less percentage remaining filling material compared with Manual Group, for all thirds (P < 0.05). The PUA protocol left similar amount of filling material among the apical, middle and cervical thirds (P > 0.05). None of the irrigation protocols tested was able to completely remove all gutta-percha/sealer from the curved canals and with isthmus area. However, the results of this study suggest that in root canals with complex anatomy that require endodontic retreatment, the PUA with orange oil, NaOCl and EDTA can be a great aid in the removal of the remaining root filling material left after removal of the bulk of filling material.